Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; états-unis

Invisible Work - Daniels, Arlene Kaplan (Social Problems, 1987)
Our folk understanding of “work” focuses on those activities you “have to do” to get paid for them. Women's work is correspondingly devalued, for it is either unpaid or limited by the demands of the unpaid work in the home. This understanding also includes a moral force. One should contribute to society by working. This paper shows the restrictiveness of these commonsense understandings and discusses the kinds of work that consequently disappear from view. I focus especially on the work involved in the social construction of daily life and in the maintenance and development of institutions. Finally, I present the rationale for expanding the concept of work to include many activities not previously considered in the folk concept: a keener awareness of the work involved in social constructions serves to dignify the labor and engender respect for the workers who do it.
Keywords: discipline; histoire et politique; philosophie; projet charge mentale; sciences humaines; thématiques; travail; travail invisible